Health-Promoting Phytonutrients Are Higher in Grass-Fed Meat and Milk - van Vliet, Stephan; Provenza, Frederick D.; Kronberg, Scott L. (Frontiers in Sustainable Food Systems, 2021)
While commission reports and nutritional guidelines raise concerns about the effects of consuming red meat on human health, the impacts of how livestock are raised and finished on consumer health are generally ignored. Meat and milk, irrespective of rearing practices, provide many essential nutrients including bioavailable protein, zinc, iron, selenium, calcium, and/or B12. Emerging data indicate that when livestock are eating a diverse array of plants on pasture, additional health-promoting phytonutrients—terpenoids, phenols, carotenoids, and anti-oxidants—become concentrated in their meat and milk. Several phytochemicals found in grass-fed meat and milk are in quantities comparable to those found in plant foods known to have anti-inflammatory, anti-carcinogenic, and cardioprotective effects. As meat and milk are often not considered as sources of phytochemicals, their presence has remained largely underappreciated in discussions of nutritional differences between feedlot-fed (grain-fed) and pasture-finished (grass-fed) meat and dairy, which have predominantly centered around the ω-3 fatty acids and conjugated linoleic acid. Grazing livestock on plant-species diverse pastures concentrates a wider variety and higher amounts of phytochemicals in meat and milk compared to grazing monoculture pastures, while phytochemicals often remain absent in meat and milk of grain-fed animals. The co-evolution of plants and herbivores has led to plants/crops being more productive when grazed in accordance with agroecological principles. The increased phytochemical richness of productive vegetation has potential to improve the health of animals and upscale these nutrients to also benefit human health. Several studies have found increased anti-oxidant activity in meat and milk of grass-fed vs grain-fed animals. Only a handful of studies have investigated the effects of grass-fed meat and dairy consumption on human health and show potential for anti-inflammatory effects and improved lipoprotein profiles. However, current knowledge does not allow for direct linking of livestock production practices to human health. Future research should systematically assess linkages between the phytochemical richness of livestock diets, the nutrient density of animal foods, and subsequent effects on human metabolic health. This is important given current societal concerns about red meat consumption and human health. Addressing this research gap will require greater collaborative efforts from the fields of agriculture and medicine.